2′-Hydroxyflavanone prevents LPS-induced inflammatory response and cytotoxicity in murine macrophages. (December 2020) - Sonowal, Himangshu; Ramana, Kota V.
Abstract: 2′-Hydroxyflavanone (2-HF) is a natural flavonoid isolated from citrus fruits. Multiple studies have demonstrated that 2-HF with its anti-proliferative and pro-apoptotic effects prevent the growth of various cancers. Although 2-HF is a well known anti-oxidative and chemopreventive agent, its role as an anti-inflammatory agent is not well established. In this study, we examined the effect of 2-HF on LPS-induced cytotoxicity and inflammatory response in murine RAW 264.7 macrophages. Flow cytometry analysis showed that pre-treatment of RAW 264.7 macrophages with 2-HF significantly prevented LPS-induced macrophage apoptosis. 2-HF also prevented LPS-induced reactive oxygen species (ROS) and nitric oxide (NO) production, lipid peroxidation, and loss of mitochondrial membrane potential in murine macrophages. Most importantly, the release of multiple inflammatory cytokines and chemokines such as eotaxin, IL-2, IL-10, IL-12p40, LIX, IL-15, IL-17, MCP-1, and TNF-α induced by LPS in the macrophages was inhibited by 2-HF. 2-HF also prevented LPS-induced activation of protein kinases p38MAPK and SAPK/JNK. Apart from this, LPS-induced phosphorylation, nuclear translocation, and DNA-binding of the redox transcription factor, NF-κB, was prevented by 2-HF. Our results demonstrate that 2-HF by regulating ROS/MAPK/NF-κB prevents LPS-induced inflammatory response and cytotoxicity in murine macrophages suggesting that the need of potential development of 2-HF as an anti-inflammatory agent to ameliorate various inflammatory complications. Graphical abstract: Unlabelled Image Highlights: 2-hydroxyflavanone (2-HF) prevents LPS –induced apoptosis of murine macrophages. 2-HF prevents LPS-induced generation of ROS, NO and lipid peroxidation. 2-HF reverses the LPS-induced decrease in mitochondrial membrane potential. 2-HF prevents LPS-induced activation of protein kinases: p38MAPK and SAPK/JNK. 2-HF prevents LPS-induced activation of NF-κB and inflammatory response.